EFL Teachers' Optimism and Commitment and Their Contribution to Students' Academic Success - Lu, Di (Frontiers in Psychology, 2021)
The present review study determines to scrutinize EFL teachers' optimism and commitment and their contribution to students' academic success. Academic optimism, as a new construct, is evolving from the examination of the positive psychology (PP), societal principal, and communal school assets that affect the attainment and success of all learners. In addition, within the past decades, commitment has received a great level of consideration, principally in the domain of structural research. The straightforward perseverance of this review is to extend the concept of academic optimism to individuals, that is, to hypothesize theoretical optimism and approve the efficacy of this paradigm at the instructor level in relation to students' academic success. According to the literature review, the definitions of these constructs, namely teachers' optimism and commitment, and students' academic success, as well as empirical studies in this domain are presented. As a conclusion, this study, to some extent, promotes the educators' mindfulness about their commitment. In this respect, pedagogical implications for teachers, school principals, teacher-trainers, and future researchers are presented, and new guidelines for further research are determined.